2015
DOI: 10.1007/s11695-015-1633-7
|View full text |Cite
|
Sign up to set email alerts
|

Expedited Biliopancreatic Juice Flow to the Distal Gut Benefits the Diabetes Control After Duodenal-Jejunal Bypass

Abstract: Expedited biliopancreatic juice flow to the distal gut was associated with augmented GLP-1 secretion and increased fasting serum TBA concentration, which may partly explain the metabolic benefits of DJB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Expedited biliopancreatic juice flow to the distal gut was associated with increased GLP-1 secretion which may partly explain the metabolic benefits of duodenal-jejunal bypass (DJB) [ 112 ]. DJB-operated diabetic rats exhibited higher glucose-stimulated GLP-1 secretion than the duodenal-jejunal anastomosis (DJA) group postoperatively [ 112 ]. Overall, metabolic surgeries are effective in improving glucose metabolism and weight loss may in part be due to the enhanced GLP-1 levels.…”
Section: Glp-1 Levels and Duodenal-jejunal Bypassmentioning
confidence: 99%
“…Expedited biliopancreatic juice flow to the distal gut was associated with increased GLP-1 secretion which may partly explain the metabolic benefits of duodenal-jejunal bypass (DJB) [ 112 ]. DJB-operated diabetic rats exhibited higher glucose-stimulated GLP-1 secretion than the duodenal-jejunal anastomosis (DJA) group postoperatively [ 112 ]. Overall, metabolic surgeries are effective in improving glucose metabolism and weight loss may in part be due to the enhanced GLP-1 levels.…”
Section: Glp-1 Levels and Duodenal-jejunal Bypassmentioning
confidence: 99%
“…Single-anastomosis duodenal jejunal bypass (DJBsa) is similar to DJB but with a simplified reconstruction method (Torres, 2019). Moreover, DJB-sa did not alter the biliopancreatic diversion or accelerate biliopancreatic flow to the lower intestine (Han et al, 2015;Weng et al, 2017). Although it has been reported that the new biliopancreatic diversion might be an effective mechanism to improve the condition of T2DM after DJB (Dubourg et al, 2013;Weng et al, 2017), DJB-sa did not display this effect.…”
Section: Introductionmentioning
confidence: 99%
“…One interesting phenomenon observed after bariatric surgery is the increase of serum total bile acids. Actually, apart from the purely restrictive procedure, adjustable gastric banding (AGB) (Kohli et al, 2013a), it has been reported that all other types of bariatric surgery are associated with postsurgical increase of serum total bile acids (Steinert et al, 2013; Albaugh et al, 2015; Ferrannini et al, 2015; Han et al, 2015). And this phenomenon has raised concern about the relationships between bile acids and bariatric surgery.…”
Section: Introductionmentioning
confidence: 99%